1989
DOI: 10.1227/00006123-198902000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hetastarch, Mannitol, and Phenylephrine on Spinal Cord Blood Flow Following Experimental Spinal Injury

Abstract: Anesthetized lambs were subjected to epidural cord compression at T13 by means of an epidural balloon distended to 200 mmHg for 80 minutes. Determinations of spinal cord blood flow (SCBF) were made by labelled microspheres prior to and during compression, and then 1/2, 1 1/2, and 2 1/2 hours after compression. Twelve control animals received saline (80 ml/h). Nine animals received hetastarch (a 20 ml/kg bolus followed by an 80 ml/h infusion) and 8 animals received mannitol (a 1 g/kg bolus followed by 1 g/kg/hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our main findings were that complete cervical SCI caused an immediate tachycardia which lasted for approximately 1 h, immediate hypotension which was sustained for the 4-h duration of the study, decreases in both systemic and pulmonary vascular resistance, and a compensatory increase in cardiac output, which resulted initially from an increase in HR but was later sustained after resolution of tachycardia by an increase in cardiac stroke volume. These data are consistent with previously published findings in adult small and large animal models as well as in humans, which consistently demonstrate reductions in HR, MAP, and systemic vascular resistance over the first few hours and in clinical studies for up to 2 weeks after SCI [3][4][5][6][7][8][9][17][18][19][20][21][22][23]. Levi et al invasively measured hemodynamics beginning 11 ± 6 h after complete and incomplete cervical SCI in adults and found that 82% required vasopressors for an average of 5.7 days after injury to maintain MAP >90 mmHg [8].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our main findings were that complete cervical SCI caused an immediate tachycardia which lasted for approximately 1 h, immediate hypotension which was sustained for the 4-h duration of the study, decreases in both systemic and pulmonary vascular resistance, and a compensatory increase in cardiac output, which resulted initially from an increase in HR but was later sustained after resolution of tachycardia by an increase in cardiac stroke volume. These data are consistent with previously published findings in adult small and large animal models as well as in humans, which consistently demonstrate reductions in HR, MAP, and systemic vascular resistance over the first few hours and in clinical studies for up to 2 weeks after SCI [3][4][5][6][7][8][9][17][18][19][20][21][22][23]. Levi et al invasively measured hemodynamics beginning 11 ± 6 h after complete and incomplete cervical SCI in adults and found that 82% required vasopressors for an average of 5.7 days after injury to maintain MAP >90 mmHg [8].…”
Section: Discussionsupporting
confidence: 92%
“…* P < 0.05 for comparisons to baseline; # P < 0.05 for comparisons between groups much of which can be attributed to differences in anesthesia, characteristics of the SCI (level, severity, and mechanism) as well as species [25][26][27][28]. Studies employing anesthetics with cardiac depressant and vasodilatory effects, such as pentobarbital, halothane, and ether have reported lower cardiac output and blood pressure after SCI [22,23,25] compared to those using ketamine or chloralose [20,29]. The relatively mild hypotension seen in our study did not require treatment and may have been due, in part, to the use of fentanyl as the main anesthetic, which is devoid of effects on cardiac contractility and systemic vascular resistance [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trauma-induced reduction of SCBF was attenuated in different animal models with various drugs including barbiturates [96], suloctidil [155], opiate antagonists such as naloxone [68,165], the calcium antagonist nimodipine [64,84], adrenoceptor agonists such as isoproterenol [45] and phenylephrine [47], as well as WEB 2170, a selective receptor antagonist of platelet-activating factor receptor [52] and MP [164].…”
Section: Improvement Of Scbfmentioning
confidence: 99%